Search for resonant pair production of Higgs bosons in the b¯bb¯b final state using pp collisions at √s=13 TeV with the ATLAS detector - Aad, G.; Abbott, B.; Abbott, D. C.; Aliev, M.; Kostyukhin, Vadim V.; Kuchinskaya, Olesya I.; Penzin, Maxim S. (Physical Review D)
A search for resonant Higgs boson pair production in the b (b) over barb (b) over bar final state is presented. The analysis uses 126 fb(-1)- 139 fb(-1) of pp collision data at root s = 13 TeV collected with the ATLAS detector at the Large Hadron Collider. The analysis is divided into two channels, targeting Higgs boson decays which are reconstructed as pairs of small-radius jets or as individual large-radius jets. Spin-0 and spin2 benchmark signal models are considered, both of which correspond to resonant HH production via gluon-gluon fusion. The data are consistent with Standard Model predictions. Upper limits are set on the production cross section times branching ratio to Higgs boson pairs of a new resonance in the mass range from 251 GeV to 5 TeV.